Picture perfect: Imaging mitochondrial membrane potential changes in retina slices with minimal stray fluorescence - Haider, Syeda Zehra; Mohanraj, Nivedha; Markandeya, Yogananda S.; Joshi, Preeti G.; Mehta, Bhupesh (Experimental eye research, 2021)
Mitochondrial membrane potential (Ψm) is a critical parameter that can be used to determine cellular well-being. As it is a direct measure of the cell's ATP generating capability, in recent years, this key component in cell biology has been the subject of thousands of biochemical and biophysical investigations. Membrane-permeant fluorescent dyes, like tetramethylrhodamine ethyl ester (TMRE), have been predominantly employed to monitor ΔΨm in cells. These dyes are typically lipophilic cationic compounds that equilibrate across membranes in a Nernstian fashion, thus accumulating into the mitochondrial membrane matrix space in inverse proportion to Ψm. However, the bath loading method practiced for labelling tissue slices with these cationic dyes poses limitations in the form of non-specificity and low signal to noise ratio, which compromises the precision of the results. Therefore, we introduce an alternative way for TMRE loading to image the ΔΨm in tissue slices by utilizing a low resistance glass pipette attached to a pressure injector. This method shows highly precise fluorescent dye labelling of the mitochondria and offers maximum output intensity, in turn enhancing signal to noise ratio.